EXPLORING FIRST-YEAR UNDERGRADUATES’ DIFFICULTIES IN WRITING THE DISCUSSION SECTION OF A RESEARCH PAPER: A SINGAPORE STUDY - Cheung Yin Ling (The English Teacher, 2013)
Much of academic writing research is conducted with academics and postgraduate students in the United States, Hong Kong, and Saudi Arabia. There is less published research on how undergraduate students reflect on their writing activities in Singapore. Little is known about what challenges these students face in writing academic papers, in particular, the discussion of results of their first academic paper written in their first year of study. The present study fills this gap by investigating Singaporean undergraduates to uncover their perception of difficulties in writing their first research papers in a compulsory academic writing course offered by a teacher training institute. In-depth interviews were conducted to the four undergraduate students. Results found that, with regard to undergraduates‟ perceptions of writing the discussions section, the main problems were selection of content, organization of content, demonstration of appropriate stance, grammar, and choice of words. Additionally, based on the instructor‟s comments on the students‟ term papers, results revealed that there were mismatches between the writing instructor‟s professional understanding and students‟ understanding of their own difficulties. The findings of this study have pedagogical implications pertaining to ways to improve the teaching of undergraduate student teachers‟ discussion of results not only in Singapore, but also in similar contexts outside Asia.